Proceedings of the 17th ACM Conference on Interaction Design and Children 2018
DOI: 10.1145/3202185.3210771
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how children interact with 3D shapes using haptic technologies

Abstract: Haptic devices have the potential to enhance the learning experience by foregrounding embodied, sensory and multi-modal elements of learning topics. In this paper, we report on-going work investigating a game prototype with haptic feedback for seven year old children's engagement with geometrical concepts as part of an iterative design study. Our findings include a new game play mode adopted by the children, that empowers the use of haptic feedback in game play and has the potential to enable the enactment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
(19 reference statements)
0
7
0
Order By: Relevance
“…It was found that children adopt different grasp styles of the haptic device than intended, which influences the control, angle, and rotation of the pen. It was also found that for typically developing children, haptic feedback presented at the same time as visual feedback tends to be overlooked [25]. These findings also reinforce the importance of determining the most intuitive design.…”
Section: Mathematicsmentioning
confidence: 64%
See 1 more Smart Citation
“…It was found that children adopt different grasp styles of the haptic device than intended, which influences the control, angle, and rotation of the pen. It was also found that for typically developing children, haptic feedback presented at the same time as visual feedback tends to be overlooked [25]. These findings also reinforce the importance of determining the most intuitive design.…”
Section: Mathematicsmentioning
confidence: 64%
“…Intuitive design can be determined via further usability research. A study conducted by Yiannoutsou et al [25], investigated young children's use of a haptic device to explore 2D and 3D shapes through a serious game designed to support geometry learning. The research aims to inform haptic educational game design by understanding the usability of the device and the ways that tactile experience shapes children's concepts of shapes.…”
Section: Mathematicsmentioning
confidence: 99%
“…Mathematics is special field of science that contains the most abstract concepts among other fields. Several studies explore the possibility of improving children conceptualization of mathematical concepts by making the abstract more tangible [34], [35]. Bodily gestures are considered as a rich source of information that both students and teachers make mostly unconsciously while expressing graphs [36], [34].…”
Section: Related Workmentioning
confidence: 99%
“…2283). In mathematics the omni Phantom has been used to support dynamic geometry learning for 10 year olds (haptic with 3D visuals) (Güçler et al 2013), trigonometry, using multimodal dynamic representations (abstract, visual and haptic) attaching haptic feedback to sine waves (Davis et al 2017), and primary school geometry learning (Yiannoutsou, Johnson and Price 2018). With adults, the vibro-tactile glove has been explored to provide a haptic sensation of tracing the borders of 3D objects, but studies suggest that long training times are needed to develop the ability to perceive shapes (Martínez et al 2016).…”
Section: Education and Trainingmentioning
confidence: 99%
“…Magnusson et al 2002). More recently the PHANToM has been used in classroom settings in the form of multimodal games for supporting visually impaired children's engagement with 3D objects tracing pathways/shapes (Patomäki et al 2004), learning geometry (Yiannoutsou et al 2018) and learning of electric circuits (Pietrzak et al 2007).…”
Section: Disability and Rehabilitationmentioning
confidence: 99%